2011
DOI: 10.1016/j.jcgg.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of delirium: Well evidenced or not?

Abstract: a b s t r a c tDelirium is a common and serious acute neuropsychiatric syndrome characterized by inattention and global cognitive dysfunction. The etiologies of delirium are diverse, multifactorial, and often reflect the pathophysiologic consequences of an acute medical illness, medical complication, or drug intoxication. At present, the diagnosis of delirium depends on the presence of certain clinical features. Many recent studies have sought to identify biomarkers for delirium to predict its onset, severity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(42 reference statements)
0
17
0
1
Order By: Relevance
“…Delirium is usually resulted from multifactorial etiopathogenesis and occurs after an acute illness, surgery, or hospitalization. Delirium may lead to loss of independence, increased morbidity and mortality, higher institutionalization, and higher health and long‐term–care costs . Postoperative delirium is frequently seen following surgery in older people and usually occurs within 5 days after surgery, especially in the first 24 to 48 hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium is usually resulted from multifactorial etiopathogenesis and occurs after an acute illness, surgery, or hospitalization. Delirium may lead to loss of independence, increased morbidity and mortality, higher institutionalization, and higher health and long‐term–care costs . Postoperative delirium is frequently seen following surgery in older people and usually occurs within 5 days after surgery, especially in the first 24 to 48 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative delirium is often preventable, so identifying risk factors for postoperative delirium may be the first and most critical step in delirium‐prevention programs . Several previous studies have shown the risk factors of postoperative delirium in older patients, which may include preoperative factors, such as age, medication use, sensory impairment, and comorbid medical conditions, and intraoperative factors, such as type of surgery, type of anesthesia, duration of operation, anemia, and the amount of blood transfused .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on inflammatory biomarkers have looked at various cytokines and chemokines. 56 A study by Van Boogaard et al divided patients into two groups, namely 'inflamed' (possessing a positive culture in a specimen of any origin, requiring antibiotics, or with more than two criteria of the systemic inflammatory response syndrome) and 'non-inflamed' (absence of the above). Of the inflammatory markers measured, in the inflamed group a raised level of interleukin-8 was associated with delirium.…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
“…55 For all biomarkers, the timing of testing may be challenging given the fluctuating course inherent to delirium. 56 Another important consideration is cost. At the time of writing, neither neuron-specific enolase (NSE) nor S100B protein tests are processed by the South Africa National Health Laboratory Service Table 4: Other delirium scoring instruments 28,32,34,37,38,44,[50][51][52] Scoring transporters, exposing the brain to potentially toxic metabolites.…”
Section: Biomarkersmentioning
confidence: 99%
“…Recognition of dehydration in the ED can be challenging, as the physical signs of dehydration, such as weight loss, decreased skin turgor, dry mucous membranes, tachycardia, and hypotension, which are very useful in assessing younger adults, are unreliable in geriatric patients (George & Rockwood, 2004). As a result, a BUN/Creatinine ratio of 18 or greater has been suggested by researchers as a threshold for identification and aggressive treatment of dehydration in delirious elderly patients (Chu et al, 2011; Marcantonio et al, 2006). …”
Section: Causes Of Acute Deliriummentioning
confidence: 99%